ANTI-DIABETIC ACTIVITIES OF THE METHANOL LEAF EXTRACTS OF HYMENOCARDIA ACIDA (TUL.) IN ALLOXAN-INDUCED DIABETIC RATS - Ezeigbo, i Ihechiluru; Asuzu, Isaac U (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The effect of methanolic extract of Hymenocardia acida leaves on diabetes and associated lipidemia were investigated on experimentally-induced diabetic rats. The extract did not demonstrate any acutely toxic effect in rats within the dose range (250 mg/kg - 2000 mg/kg) employed in the study; hence it was well tolerated by the rats. In all experiments, the anti-diabetic effects were dose-dependent and comparable to that of glibenclamide (2 mg/kg) standard. At a dose of 500 mg/kg, lipid profile markers such as the serum total cholesterol (TC) levels, LDL-C, triglycerides and HDL-C were significantly lower (p <0.05) than those of both the treated and untreated controls.